Co-ordination of Health Services Liverpool : Child Welfare
1928-03 1928 1920s 6 pages -2- At one of the nurseries, children may be boarded for short periods to tide over special difficulties in the homes - usually illness of the mother. Daily or weekly charge made for each child. Institutions greatly appreciated by working class mothers, when by reason of widowhood, or unemployment or incapacity of their husbands they are compelled to go out to work in order to make provision for themselves or their families. Children who attend are taught good manners, clean habits, etc., diet, rest, play and progress being carefully supervised. These nurseries provide a training school for nursery nurses and an excellent preliminary training for girls wishing to become subsequently hospital nurses. MILK DEPOTS. A supply of milk is given on the presentation by the applicant of a note from a doctor, and in a few instances it is allowed on production of a written request from a midwife. On one day in each week mothers attend at the centre in their district for the purpose of reviewing family circumstances when the supply of milk is continued at the price being charged - or if circumstances improved - charge increased; if circumstances worse than when last reviewed - charge lowered. Usual grant is for a period of 4 or 6 weeks. Exceptional cases 2 or 8 weeks. It will be seen from the facts quoted above that the activities organised by the Health Committee of Liverpool for the welfare of mothers, infants and young children are gratifying in results. It is necessary for the fulfilment of a complete welfare scheme to have co-ordination between the clinics, private doctors, hospitals, maternity and rest homes, midwives, guardian of the poor and all those agencies which render valuable assistance to the medical and social needs of necessitous persons. 292/824/1/119